Memory and Social Movements in Modern and Contemporary History
XIX, 306 p. 33 illus., 29 illus. in color.
Keywords: Reflecting the growing interest of historians in memory studies, this edited collection examines the relationship between memory and global social movements from 1848 to the present. For a long time, there has been little attempt by historians to consider memory and social activism in an integrated, systematic, and comparative way. However, in recent years, scholars have demonstrated that social movements rely on collective memories to assert claims, mobilize supporters, and legitimize their political visions, while also helping to further shape collective memories. This book delves into the synergies between memory studies and social movements, exploring how social movements have been constructing and creating memories of their own activity, how specific landscapes of memory have influenced social movements, and how activists have used memory as a cultural resource to further their own goals and ambitions. The case studies presented cover a range of different types of political activism, including the fights for workers’, gay, feminist, and pacifist rights, as well as ecological, urban, and far-right movements across the globe, portraying the diverse interrelations that exist between social movements and collective memory. Stefan Berger is Professor of Social History and Director of the Institute for Social Movements at Ruhr-Universitaet Bochum, Germany, as well as Honorary Professor at Cardiff University, UK. He is also Executive Chair of the Foundation History of the Ruhr. He has published widely on the comparative history of social movements, in particular labour movements as well as national(ist) movements, the history of nationalism and national identity, deindustrialisation studies, and memory studies. Christian Koller is Director of the Swiss Social Archives (Zurich), Adjunct Professor of Modern History at the University of Zurich, and part-time Lecturer in Social History at the Swiss Open University. He has published widely on labour history, the history of racism and nationalism, historical semantics, sports history, the history of colonial armies, the First World War, urban history and in the field of archival and library sciences.